National Lipid Association Recommendations for Patient-Centered Management of Dyslipidemia: Part 2 - Jacobson, Terry A.; Maki, Kevin C.; Orringer, Carl E.; Jones, Peter H.; Kris-Etherton, Penny; Sikand, Geeta; La Forge, Ralph; Daniels, Stephen R.; Wilson, Don P.; Morris, Pamela B.; Wild, Robert A.; Grundy, Scott M.; et al. (Journal of clinical lipidology, 2015)
An Expert Panel convened by the National Lipid Association previously developed a consensus set of recommendations for the patient-centered management of dyslipidemia in clinical medicine (part 1). These were guided by the principle that reducing elevated levels of atherogenic cholesterol (non–high-density lipoprotein cholesterol and low-density lipoprotein cholesterol) reduces the risk for atherosclerotic cardiovascular disease. This document represents a continuation of the National Lipid Association recommendations developed by a diverse panel of experts who examined the evidence base and provided recommendations regarding the following topics: (1) lifestyle therapies; (2) groups with special considerations, including children and adolescents, women, older patients, certain ethnic and racial groups, patients infected with human immunodeficiency virus, patients with rheumatoid arthritis, and patients with residual risk despite statin and lifestyle therapies; and (3) strategies to improve patient outcomes by increasing adherence and using team-based collaborative care.